State bureaucracy and black labour in South Africa: The milling workers' strike of 1944 - Duncan, David (My University, 1989)
In September 1944, African milling workers on the Rand, in Pretoria and in several other centres in the Transvaal, went on strike. The stoppage lasted only a few days, but it involved over 1200 hundred labourers more than half of whom mere arrested. The strike was supported by the Council for Non-European Trade Unions (CNETU), the Trades and Labour Council (TLC), the Communist Party, the Campaign for Right and Justice (CRJ), and various religious denominations. It attracted the attention of politicians at the highest level, and disrupted supplies of a basic commodity to the general public. The ending of the stoppage was confused, with compromises on both sides and appeals to official arbitration. Within four months, though, the workers were receiving a few shillings more each week in their pay packets. This study focuses on the role of the State bureaucracy before and during the milling dispute. The Department of Labour was chiefly involved in the run up to the strike and in its settlement. During the actual stoppage, the Native Affairs Department (NAD) was much to the fore, with subsidiary parts for the South African Police, the Justice Department, and the Prime Minister's office. All five had also been involved in the coal distributors' strike three months earlier, which helped to shape the tactics adopted by officials during the milling dispute.
African Studies Seminar series. Paper presented 31 July, 1989
Keywords: Labor. South Africa; Strikes and lockouts. South Africa. Transvaal